Malignant Pleural Mesothelioma. Case Report and Literature Review - Samuel Sánchez Sánchez; Liz María Calvo Díaz; Ana Laura Navarro Baldellot (Revista Finlay)
Pleural mesotheliomas are primary mesothelial cell tumors. Lining the pleural cavity, they are closely related to asbestos exposure. They have a low incidence and poor prognosis. A 46-years-old patient, white-skinned, who attended the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos due to pain in the back and shoulders, fever, and weight loss is presented. The physical examination revealed an abolished vesicular murmur in the lower 1/3 of the right lung. The chest X-ray and CT scan showed a medium to large right pleural effusion and pleural thickening. Histological studies indicated that the lesion was compatible with epithelioid variant pleural mesothelioma. The patient is maintained with cytostatic treatment and follow-up in consultation. The objective of this study is to describe the case of a patient with malignant pleural mesothelioma, admitted to the Internal Medicine Service of the Dr. Gustavo Aldereguía Lima General University Hospital of Cienfuegos.